Pemikiran Syekh Ali Jum’ah Tentang Fatwa Jual Beli Khamr di Negara Non Muslim - Faiqoh, Ulfia Nur (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2021)
The discussion about the fatwa legalizing the sale and purchase of khamr in non-Muslim countries by contemporary Egyptian cleric Sheikh Ali Jum'ah caused various reactions. In February 2021, Indonesia allowed investment in the liquor industry as stipulated in Presidential Regulation Number 10 of 2021 concerning the Investment Business Sector. After this policy was issued, it became a long topic that was discussed in Indonesia because it had a different view from the ulema of the archipelago. The ijtihad method used by Sheikh Ali Jum'ah in this problem is the Intiqa'i method and the Insya'i method with considerations of benefit and eliminating difficulties using the legal basis of the opinion of Imam Abu Hanifah and Muhammad bin Hasan ash-Syaibani from the hadith of the Prophet Muhammad that there is no usury between Muslims and non-Muslims in war zones. This writing aims to find out the basis for the permissible sale and purchase of khamr in non-Muslim countries according to Sheikh Ali Jum'ah. The method used by the author is normative juridical which is carried out by examining and interpreting theoretical matters concerning principles, conceptions, doctrines, and legal norms related to research. The sale and purchase of khamr in non-Muslim countries is included in maqashid sharia dharuriyat and maslahah mulghah, namely maslahah that causes benefit but is not in accordance with syar'i, that the law of khamr is still haram because it is qat'i so it cannot be takhsis.Keywords: Selling and Purchasing, Khamr, Ali Jum’ah